2016
DOI: 10.1038/nature19787
|View full text |Cite
|
Sign up to set email alerts
|

Asthenosphere rheology inferred from observations of the 2012 Indian Ocean earthquake

Abstract: The concept of a weak asthenospheric layer underlying Earth's mobile tectonic plates is fundamental to our understanding of mantle convection and plate tectonics. However, little is known about the mechanical properties of the asthenosphere (the part of the upper mantle below the lithosphere) underlying the oceanic crust, which covers about 60 per cent of Earth's surface. Great earthquakes cause large coseismic crustal deformation in areas hundreds of kilometres away from and below the rupture area. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 40 publications
6
68
0
Order By: Relevance
“…One of the best locations for studying oceanic mantle rheology is the Indian Ocean, where a large M w 8.6 earthquake occurred in 2012 (e.g., Meng et al 2012). Two recently published papers regarding oceanic mantle rheology analyze the postseismic deformation following the 2012 Indian Ocean earthquake (Hu et al 2016b;Masuti et al 2016). …”
Section: Assessment Of Viscoelastic Structurementioning
confidence: 99%
“…One of the best locations for studying oceanic mantle rheology is the Indian Ocean, where a large M w 8.6 earthquake occurred in 2012 (e.g., Meng et al 2012). Two recently published papers regarding oceanic mantle rheology analyze the postseismic deformation following the 2012 Indian Ocean earthquake (Hu et al 2016b;Masuti et al 2016). …”
Section: Assessment Of Viscoelastic Structurementioning
confidence: 99%
“…In the multiple‐mechanism models we consider below, we will further examine the trade‐off between D and ηmLCT. For the sake of simplicity, we assume the ratio of the steady state transient viscosity ηmLCT to the transient viscosity ηkLCT in the Burgers body is a constant and follow Hu, Bürgmann, Banerjee, et al () and Hu, Bürgmann, Uchida, et al () and use ηmLCTtrue/ηkLCT = 10, which is also the same value we obtain for the upper mantle beneath Tibet.…”
Section: Model Resultsmentioning
confidence: 96%
“…Hu, Bürgmann, Uchida, et al () reported a mantle wedge viscosity of 3 × 10 19 Pa s for Japan, the same as in this study, through modeling the viscoelastic postseismic deformation of the 2011 Mw9.0 Tohoku earthquake. They found that the oceanic upper mantle may include an 80‐km thick top layer with a viscosity of 2 × 10 18 Pa s overlying a more rigid layer with a viscosity of 10 20 Pa s Hu, Bürgmann, Banerjee, et al (). The asthenospheric properties obtained in this work thus may be representative of other tectonically active regions.…”
Section: Discussionmentioning
confidence: 99%